EFFECTIVITY AND PRODUCT DIVERSIFICATION OF THE BIOLOGICAL POLLINATOR OF Apis mellifera L. IN TORAJA COFFEE PLANTATION MONOCULTURE - Budiaman . (Jurnal Silvikultur Tropika, 2016)
Plant flowers and another part of plant in the form of nectar, ekstranutfialnectar, resin and or pollen were abundant and still wasted in the Toraja coffee plantation monoculture Coffea arabica Usda. Apis mellifera L. honey bees is known as one of biology pollinator is easily manipulated and can convert plant flowers into products of high economic value, but its effectivity as a biology pollinator, unknown in monoculture plantations Toraja coffee C. arabica Usda. The purpose of this study was to evaluate the efficacy and product production of biology pollinator of the A. mellifera L. honey bees in Toraja coffee monoculture plantations. Analysis of data to distinguish between treatments (pollination with bees) with no bees used testing the equality of two average t-distribution. The results showed that the the management of A. mellifera L. honey bees as biology pollinator in Toraja Coffee plantations C. arabica Usda , is very effective in improving the quantity amounted to 18.75 % and quality amounted 6.4 % of the coffee fruit production per season. The amount of production diversification of A. mellifera L. honey bees in Toraja coffee plantations are 5 types of products with an average amount of production, ie 0.85 kg of honey, bee pollen 0.51 kg, 0.37 kg beeswax, propolis 0.21 kg and 0.15 kg of bee venom per colony per flowers season.Key words: effectivity, product diversification and biology pollinator.